2019
DOI: 10.3390/sym11091066
|View full text |Cite
|
Sign up to set email alerts
|

Deep Metric Learning: A Survey

Abstract: Metric learning aims to measure the similarity among samples while using an optimal distance metric for learning tasks. Metric learning methods, which generally use a linear projection, are limited in solving real-world problems demonstrating non-linear characteristics. Kernel approaches are utilized in metric learning to address this problem. In recent years, deep metric learning, which provides a better solution for nonlinear data through activation functions, has attracted researchers' attention in many dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
263
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 473 publications
(266 citation statements)
references
References 84 publications
(111 reference statements)
2
263
0
1
Order By: Relevance
“…The concept of deep metric learning was introduced when deep learning and metric learning were combined [34]. As such, the performance of a deep metric learning model depends not only on the quality of image dataset and the deep network architecture, but also on the metric loss function used in the learning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The concept of deep metric learning was introduced when deep learning and metric learning were combined [34]. As such, the performance of a deep metric learning model depends not only on the quality of image dataset and the deep network architecture, but also on the metric loss function used in the learning.…”
Section: Discussionmentioning
confidence: 99%
“…Loss function is one of the most important functions in deep feature learning. In general, the models presented in the the domain of deep metric learning can be categorised as minimising either the contrastive loss or the triplet loss [33,34]. If the contrastive loss L C [35] function is selected, the model is penalised differently based on whether the classes of the samples are the same or different.…”
Section: Deep Metric Embeddingsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of research, a number of loss functions have been proposed. Kaya M et al [21] combined with recent research results, revealed the importance of deep metric learning and summarized the current problems dealt with in this filed. For instance, the contrastive loss [22,23] captures the similarity or dissimilarity between pairwise of samples, while the triplet-based loss [12,24] describes the relationship among the triple samples.…”
Section: Introductionmentioning
confidence: 97%
“…However, no effort has been dedicated to tackling the issue of limited training data. Recent advancements in meta-learning and metric learning [7] have paved the way for addressing the data scarcity issue [8]. Training HPFs 35 311 Test HPFs 15 295 Training mitoses 226 550 Test mitoses 101 533 In this work, we investigate deep metric learning and propose a classification method for mitosis detection utilizing both class label information and local spatial distribution information between training samples, to be able to learn from fewer annotations.…”
Section: Introductionmentioning
confidence: 99%